Development of the Korean Practice Parameter for Adult Attention-Deficit/Hyperactivity Disorder - Bahn, Geon Ho; Lee, Young Sik; Yoo, Hanik K.; Kim, Eui-Jung; Park, Subin; Han, Doug Hyun; Hong, Minha; Kim, Bongseog; Lee, Soyoung Irene; Bhang, Soo Young; Lee, Seung Yup; Hong, Jin Pyo; et al. (Journal of korean Academy of Child and Adolescent Psychiatry, 2020)
Adult attention-deficit/hyperactivity disorder (ADHD) is an important mental health problem that needs resolution, especially considering the high rates of ADHD continuation from childhood to adolescence/adulthood and the high prevalence of ADHD in adults. Adults with ADHD have lifelong negative impacts and require close monitoring with long-term follow-up. Hence, the establishment of a Korean practice parameter for adult ADHD is necessary to minimize discontinuation of treatment and enable information sharing among Korean mental health professionals. The Korean practice parameter was developed using an evidence-based approach consisting of expert consensus survey coupled with literature review. According to the expert consensus survey, the most commonly used diagnostic methods were clinical psychiatric interview (20.66%) and self-report scales (19.25%) followed by attention (14.71%) and psychological tests (14.24%). Key evaluation instruments currently available in Korea are the World Health Organization Adult ADHD Self-Report Rating Scale, Korean Adult ADHD Rating Scale, Diagnostic Interview for ADHD in Adults, Barkley Deficits in Executive Functioning Scale for adults, Comprehensive Attention Test, Conners' Continuous Performance Test, and the subtests of Wechsler Adult Intelligence Scale, Digit Span and Letter-Number Sequencing. Although pharmacotherapy is recommended as the first-line of treatment for adult ADHD, we recommend that it be followed by a multimodal and multidisciplinary approach including psychoeducation, pharmacotherapy, cognitive behavior therapy and coaching. The Korean practice parameter introduces not only general information for the diagnosis and treatment of adult ADHD on a global scale, but also the process of diagnosis and treatment options tailored to the Korean population.